An Allele of Arabidopsis COI1 with Hypo- and Hypermorphic Phenotypes in Plant Growth, Defence and Fertility - Dobón, Albor (Public Library of Science, 2013)
Resistance to biotrophic pathogens is largely dependent on the hormone salicylic acid (SA) while jasmonic acid (JA) regulates resistance against necrotrophs. JA negatively regulates SA and is, in itself, negatively regulated by SA. A key component of the JA signal transduction pathway is its receptor, the COI1 gene. Mutations in this gene can affect all the JA phenotypes, whereas mutations in other genes, either in JA signal transduction or in JA biosynthesis, lack this general effect. To identify components of the part of the resistance against biotrophs independent of SA, a mutagenised population of NahG plants (severely depleted of SA) was screened for suppression of susceptibility. The screen resulted in the identification of intragenic and extragenic suppressors, and the results presented here correspond to the characterization of one extragenic suppressor, coi1-40. coi1-40 is quite different from previously described coi1 alleles, and it represents a strategy for enhancing resistance to biotrophs with low levels of SA, likely suppressing NahG by increasing the perception to the remaining SA. The phenotypes of coi1-40 lead us to speculate about a modular function for COI1, since we have recovered a mutation in COI1 which has a number of JA-related phenotypes reduced while others are equal to or above wild type levels.